Management of hip fractures in the elderly. Issue 9 (September 2016) - Chesser, Tim; Chauhan, Govind; Kelly, Michael
Abstract: A fracture of the proximal femur (or hip fracture) is a devastating injury to an elderly patient. Nearly all patients require surgery as part of their treatment but their care necessitates complex multidisciplinary involvement. In the last ten years there have been a number of initiatives to help improve care for this challenging patient group, as well as establishment of The National Hip Fracture Database, to allow us to audit the care provided. With this focus, we have seen both mortality and length of stay decrease. The aim of this article is to summarize the current recommendations for patients who suffer a hip fracture.